ANALISIS KISAH NABI YUSUF DALAM AL-QURAN MELALUI PENDEKATAN INTERDISIPLINER PSIKOLOGI SASTRA - Mahliatussikah, Hanik (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2016)
The emergence of psycho-literature study is in line with the relation between psychology and literature. Psychoanalysis theory used in this study was the theory of Sigmund Freud to examine the character of Yusuf. This theory distinguished three kinds of personality; they are id, ego, and superego. This research investigated Yusuf's behavior in the context of citizenship. The story of Yusuf is determined as the best story from the aspect of its styles, contents, and objectives. This story was begun with the dream of Yusuf, sunk into the well, sold to Egyptian merchant, flirted by the wife of his merchant, found by his family, and the lessons of his story. In its relation to Islam, superego in the theory of Freud should be aimed to Islamic values. The principle of tauhid should always be in mind, so when bed desire comes to a moslem, then that principle will be the savior. Psycho-literature interdisciplinary study uncovers psychological aspects of Yusuf to take the lessons for the society.DOI: 10.24865/ajas.v1i2.13